1999
DOI: 10.1128/aem.65.12.5242-5246.1999
|View full text |Cite
|
Sign up to set email alerts
|

cis -Chlorobenzene Dihydrodiol Dehydrogenase (TcbB) from Pseudomonas sp. Strain P51, Expressed in Escherichia coli DH5α(pTCB149), Catalyzes Enantioselective Dehydrogenase Reactions

Abstract: cis-Chlorobenzene dihydrodiol dehydrogenase (CDD) fromPseudomonas sp. strain P51, cloned into Escherichia coli DH5α(pTCB149) was able to oxidizecis-dihydrodihydroxy derivatives (cis-dihydrodiols) of dihydronaphthalene, indene, and fourpara-substituted toluenes to the corresponding catechols. During the incubation of a nonracemic mixture ofcis-1,2-indandiol, only the (+)-cis-(1R,2S) enantiomer was oxidized; the (−)-cis-(S,2R) enantiomer remained unchanged. CDD oxidized both enantiomers ofcis-1,2-dihydroxy-1,2,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The enantioselective oxidation of dihydrodiols was also investigated for chlorobenzene cis-dihydrodiol dehydrogenase (TcbB) from Pseudomonas sp. strain P51 and it was found that the enantioselectivity of the conversion is highly dependent on the substrate (Raschke et al 1999). TcbB exclusively oxidizes (+)-cis-(1R,2S)-indandiol, whereas both enantiomers of cis-1,2-dihydroxy-1,2,3,4tetrahydronaphthalene are converted.…”
Section: Enantioselective Enzymesmentioning
confidence: 99%
“…The enantioselective oxidation of dihydrodiols was also investigated for chlorobenzene cis-dihydrodiol dehydrogenase (TcbB) from Pseudomonas sp. strain P51 and it was found that the enantioselectivity of the conversion is highly dependent on the substrate (Raschke et al 1999). TcbB exclusively oxidizes (+)-cis-(1R,2S)-indandiol, whereas both enantiomers of cis-1,2-dihydroxy-1,2,3,4tetrahydronaphthalene are converted.…”
Section: Enantioselective Enzymesmentioning
confidence: 99%
“…It should be pointed out that although data for H-4 in the description of related natural products is given as either a multiplet or a broad singlet, this proton has also been described as a triplet of doublets in cases such as compound 34 [28] (Figure 3). This assignment was supported by comparison of the 1 H and 13 C NMR spectroscopic data of compound 12 with those of ketone 35, also with a cis relationship of Me-18 and H4 (numbering of pseudopterosins) (Table 2) [10]. The high diastereoselection observed in the cuprate addition to α,β-unsaturated esters 22 and 24 may be explained by attack of the reagent from the Re-face of the starting materials in their minimum energy conformation, probably due to severe steric interactions with the aromatic moiety in the Si approach.…”
Section: Methodsmentioning
confidence: 65%
“…The configuration of compound 23 as 1R*11R* was firstly deduced by comparison of the 1 H and 13 C NMR spectroscopic data of this compound with helioporin D 7 (corrected [8] and previously reported structure [1]) (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations